Effectiveness of Technolas torsional eye tracking system on visual outcomes after photorefractive keratectomy - Gharaee, Hamid (J Curr Ophthalmol, 2016)
PURPOSE: To investigate the efficacy of Technolas 217Z eye tracking system (torsional component) in corneal surface irregularity and high order aberrations (HOAs) after photorefractive keratectomy METHODS: Patients with compound myopic astigmatism among persons demanding refractive surgery in Khatam-al-Anbia Eye Hospital with the mean age of 29 years were enrolled in this double-blind randomized interventional study. The mean spherical equivalent (SE) of refractive error was −4.75 diopters(D) (range: −1.5 to −7.0), and the mean astigmatism was 3 D (range:1.0–4). Many studies were performed for each patient including: A complete eye examination, visual acuity and Monocular contrast sensitivity evaluation, and refraction. Corneal topography, Orbscan II, and wavefront aberrometry were conducted. One eye was randomly assigned for aspheric treatment and applying eye tracking system. The other eye was treated without torsional eye tracking system. The outcome measures were uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), contrast sensitivity, corneal irregularity index in 3 mm and 5 mm optical zones in Orbscan II, and mean total HOAs at the 6-monthvisit. RESULTS: Fifty eyes of 25 patients were enrolled. Mean UCVA was improved significantly in both the study and control groups in the 6-month post-operative follow-up. There was no significant difference between the 2 groups in UCVA and BCVA (P = 0.185 and P = 0.176, respectively). Total HOAs increased in both groups after PRK. However, they were lower in eyes treated with the eye tracking system (P < 0.001). Corneal irregularity index in 3 mm and 5 mm central zones in Orbscan II was significantly lower in the study group (P = 0.045 and P = 0.031 respectively). Contrast sensitivity function was not different in the 2 groups (P = 0.15). CONCLUSION: Our study findings suggest that applying ‘Technolas 217z’ eye tracker system (Bausch and Lomb Advanced) results in a more regular anterior surface of cornea. Therefore, we recommend it for surface laser refractive surgery.